A Novel Antimicrobial Peptide Scyreprocin From Mud Crab Scylla paramamosain Showing Potent Antifungal and Anti-biofilm Activity - Yang, Ying; Chen, Fangyi; Chen, Hui-Yun; Peng, Hui; Hao, Hua; Wang, Ke-Jian (Frontiers in Microbiology, 2020)
Natural antimicrobial peptides (AMPs) are potential antibiotic alternatives. Marine crustaceans are thought to generate more powerful and various AMPs to protect themselves from infections caused by pathogenic microorganisms in their complex aquatic habitat, thus becoming one of the most promising sources of AMPs or other bioactive substances. In the study, a novel protein was identified as an interacting partner of male-specific AMP SCY2 in Scylla paramamosain and named scyreprocin. The recombinant product of scyreprocin (rScyreprocin) was successfully expressed in Escherichia coli. rScyreprocin exerted potent, broad-spectrum antifungal, antibacterial, and anti-biofilm activity (minimum inhibitory concentrations from 0.5 to 32 μM) through differential modes of action, including disruption of cell membrane integrity and induction of cell apoptosis, and has rapid bactericidal (in 0.5–2 h) and fungicidal (in 8–10 h) kinetics. In addition to its fungicidal activity against planktonic fungi, rScyreprocin also prevented the adhesion of fungal cells, inhibited biofilm formation, and eradicated the mature biofilms. Moreover, rScyreprocin showed a profound inhibitory effect on spore germination of Aspergillus spp. (minimum inhibitory concentrations from 4 to 8 μM). This peptide was not cytotoxic to murine and mammalian cells and could increase the survival rate of Oryzias melastigma under the challenge of Vibrio harveyi. Taken together, the novel AMP scyreprocin would be a promising alternative to antibiotics used in aquaculture and medicine.